Phytoremediation of heavy metals with several efficiency enhancer methods - Karami, Ali; Shamsuddin, Zulkifli (Academic Journals, 2010)
It is no doubt that the contamination of water, air and soil has worsened, and this occurs as a result of the increase in population. However, the need for remediation technologies has to be seriously considered. Phytoremediation is one of the remediation techniques with a relatively slow procedure and low efficiency. This review covers some of the biological, chemical, physical, physico-chemical and genetic methods, which were applied in parallel with phytoremediation, in an attempt to help increase the efficiency in the remediation of air, soil and water. These include lowering the pH and increasing the electrode potential (Eh), as well as using chelating agents and micro-organisms (arbuscular mycorrhizal fungi (AMF) and plant growth promoting rhizobacteria (PGPR)). Among the introduced methods, an appropriate application of the PGPRs is one of the most useful and environmentally friendly techniques which is currently considered as a useful process in phytoremediation. As a result of the discovering of these new methods, multi-approaches have been executed for a faster and higher removal rate of the contaminants, with a consequent increase in the efficiency of phytoremediation, as compared to single techniques.